Predictor-based control of stochastic systems with nonlinear diffusions and input delay. (September 2019) - Cacace, Filippo; Germani, Alfredo; Manes, Costanzo; Papi, Marco
Abstract: We consider the problem of state-feedback control of linear continuous-time stochastic systems with nonlinear diffusion terms affected by time-varying input delays or, equivalently, by time-varying state measurement delays. We propose a finite-dimensional control law based on closed-loop predictors and derive sufficient delay bounds for the exponential stability in mean and exponential mean square stability with prescribed rate.